The effects of park improvement on park use and park-based physical activity - Arifwidodo, Sigit Dwiananto; Chandrasiri, Orana (Journal of Architecture and Urbanism, 2021)
Park is considered as one of the necessary settings in the urban area to promote physical activity and a healthy lifestyle. It provides opportunities to engage in park-based physical activity to a wide range of users. Studies have found that park improvement is a sustainable way to increase the urban population’s physical activity levels. This study explores the effects of park improvement on park use and park-base physical activity using Benjakitti Park, one of the major district parks in Bangkok, Thailand, as the case study. The park improvement was designed and constructed from October 2016 – January 2017. A System for Observing Play and Recreation in Communities (SOPARC) observations were used to observe the changes in park use and park-based physical activity before and after the park improvement. It was found that park improvement changed users’ characteristics and the patterns of park use and park-based physical activity. The park improvement was associated with an increasing number of children and elderly visitors and a 4.1% and 17.6% increase in cycling and running. The project shows that even a tiny improvement in the built environment can change people’s attitude and behaviour towards physical activity and a healthy lifestyle.